4(x-4)+x=5(x-5)+9

Simple and best practice solution for 4(x-4)+x=5(x-5)+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-4)+x=5(x-5)+9 equation:


Simplifying
4(x + -4) + x = 5(x + -5) + 9

Reorder the terms:
4(-4 + x) + x = 5(x + -5) + 9
(-4 * 4 + x * 4) + x = 5(x + -5) + 9
(-16 + 4x) + x = 5(x + -5) + 9

Combine like terms: 4x + x = 5x
-16 + 5x = 5(x + -5) + 9

Reorder the terms:
-16 + 5x = 5(-5 + x) + 9
-16 + 5x = (-5 * 5 + x * 5) + 9
-16 + 5x = (-25 + 5x) + 9

Reorder the terms:
-16 + 5x = -25 + 9 + 5x

Combine like terms: -25 + 9 = -16
-16 + 5x = -16 + 5x

Add '16' to each side of the equation.
-16 + 16 + 5x = -16 + 16 + 5x

Combine like terms: -16 + 16 = 0
0 + 5x = -16 + 16 + 5x
5x = -16 + 16 + 5x

Combine like terms: -16 + 16 = 0
5x = 0 + 5x
5x = 5x

Add '-5x' to each side of the equation.
5x + -5x = 5x + -5x

Combine like terms: 5x + -5x = 0
0 = 5x + -5x

Combine like terms: 5x + -5x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 9=p+15 | | (4+u)(5u-8)=0 | | -3x^6-9x^5+120x^4=0 | | 7x^2-11x-26=0 | | 11(x-4)=121 | | a^2-16ax+60x^2=0 | | s^2+11sd+28d^2=0 | | 47-T=T-6 | | (x)(x)-25=0 | | 47+(t-6)=T | | q=4.7 | | -4(n-2)=2-3n | | 6x+90-x=180 | | 4(-2+1.25y)+6=5y-2 | | 8x+5=4x+3 | | 15=7a+3-1a | | 47q=47+q | | (5)y*y-y-4=0 | | 2(x+8)+7=2x+5 | | 3y-12=(-2y)+(-12) | | 24x-15= | | 3y-12=-2y+(-12) | | 1.5x^2+60x-190=0 | | (3)t*t-7t-20=0 | | 832=(x+10-4)(x-4)(2) | | -2y(3+4)=5x+2 | | 4x+6=5y-2 | | 3k-5=-8(6+5n) | | 9-16x-7-5x=5 | | 832=30*20*2 | | 6x+5=0.5x(x+6)-4 | | -55=8+7(k-5) |

Equations solver categories